Investigating the Effect of Learner-Centered Activity on EFL Primary School Pupils’ Engagement. The Case of Fourth Year at Mohmmed Ben Chainoune Primary School. - Ms. Bochra Zineb OUKALI; Ms. Zineb Lina OUAHABI (My University, 2025)
Abstract The current study investigates the effect of learner-centered approach (LCA) on English as a Foreign Language (EFL) primary school pupils' engagement. The case study of fourth year primary school pupils. The main objective of the present study is to examine teachers' perceptions of the use of LCA and determine its effectiveness on EFL primary school pupils' engagement. A holistic theoretical framework is reviewed to provide insights about the two variables: Learner-Centered Approach and Pupils Engagement, highlighting their both definitions and importance, features of LCA and dimensions of engagement. This descriptive study employs a qualitative approach, incorporating interviews and classroom observations conducted with a sample of thirty-five (35) fourth year primary school pupils and fourteen (14) EFL primary school teachers during the academic year 2024-2025 under normal conditions. After analyzing the data gathered from the research instruments, findings reveal that teachers view LCA as an essential and effective teaching approach, and the implementation of this approach in EFL primary school classes is effective on pupils' engagement, when they actively participate, understand better and show interest and motivation. Based on the results, the study inform recommendations for addressing curriculum gaps, incorporating formative assessment and extending session durations. However, the study notes certain limitations which include the short duration of the session, the impact of small sample size on the generalizability of the results and the research short period which may affect the observation of the long-term effect of LCA. In spite of the mentioned limitations, the study offers significant insights for the implementation of LCA in EFL primary school education.
Keywords: Keywords: Learner-Centered Approach; Pupils' engagement; EFL learners; English as a Foreign Language; EFL teachers; Teachers' perceptions; Features of LCA; Dimensions of engagement; Active participation; The implementation of LCA.